HUBUNGAN KEKERABATAN PISANG AMBON LOKAL DI KABUPATEN REJANG LEBONG BERDASARKAN KARAKTERISASI MORFOLOGI - Suryani, Rini; Suliansyah, Irfan; Warnita; Zainal, Aprizal; Sukartini (Akta Agrosia, 2023)
Morphological characterization is initial information in finding diversity and determining desired superior characters. The purpose of the research is to conduct morphological characterization and determine the relationship of local Ambon banana in Rejang Lebong District. Neko77 This study was conducted during September to October 2019, utilizing a field survey method with purposive sampling to investigate the morphological characterization and determine the relationship of local Ambon bananas in Rejang Lebong District. The kinship relationship of each type of local banana, Ambon เว็บสล็อต | R4shub Curup consists of 3 related groups, where 1st group belongs toAmbon Kuning (1), Ambon Curup (7), Ambon Hijau (2) and Ambon Lumut (6), 2nd group is Ambon Pendek (5), and the 3rd group belongs toAmbon Putih (3), and Ambon Dingin (4). The closest kinship is between Ambon Kuning (1) and Curup (7), with a similarity level of 93,67 %, while the Ambon Curup owns the farthest kinship level with Ambon Pendek (5), which is 48,37%. The high genetic diversity is caused by the frequent occurrence of random inter-species mating. Keywords: Identification, morphology, kinship relationship, local ambon banana, Rejang Lebong